PENGEMBANGAN MEDIA INTERAKTIF CANVA DALAM PEMBELAJARAN LITERASI MEMBACA DI SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on Canva to improve reading literacy of second-grade students at SDN 009 Sendayan. The development of this media was motivated by the low reading interest of students and the absence of supporting media in Indonesian language learning, which resulted in a less conducive classroom atmosphere and decreased student focus. This research used a Research and Development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects of the study were 22 second-grade students and one classroom teacher. The results showed that the Canva-based interactive media developed was rated as “highly feasible” by material and media experts. Classroom implementation demonstrated an increase in student interest and engagement in reading activities, indicated by improved learning outcomes and high student enthusiasm during the learning process. The media also created a more enjoyable and interactive learning environment, making it easier for students to understand reading content. Therefore, the use of Canva-based interactive media is effective as an innovative tool for teaching Indonesian language to enhance reading literacy in elementary school. Keywords: Interactive Media, Canva, Reading Literacy,